A STUDY OF GROSS POSTMORTEM FINDINGS IN CASES OF HANGING AND LIGATURE STRANGULATION DEATHS (Journal of Forensic Medicine & Toxicology, 2016)
Hanging remains to be one of the common methods of committing suicide while strangulation is predominantly homicidal. Hence all cases of hanging are considered suicidal until the contrary is proved. Meticulous dissection and sharp distinction between hanging and strangulation is warranted during autopsy. A prospective study was conducted at the Department of Forensic Medicine, P.D.U. Medical College & Hospital, Rajkot from January 2008 to December 2008. During that period out of 2159 cases, 90 cases of hanging and 7 cases of ligature strangulation were selected for the present study. We found that deaths due to hanging constituted 4.17% of the total unnatural deaths subjected to medicolegal autopsy; young adults, of the age group 21 to 30 years accounted for the maximum cases, 40%; and the male: female ratio was 2:1. Chunni (34.44%) was the most common ligature material used. The mark was obliquely placed (100% cases) above thyroid cartilage (80% cases). In all the cases of ligature strangulation, the mark was transverse, below the level of thyroid cartilage.Dribbling of saliva present in 55 cases (61.11%) of hanging, bleeding from mouth and nose found in 7 cases (100%) of ligature strangulation, involuntary discharge of urine present in 10 cases (11.11%) of hanging, involuntary discharge of fecal matter present in 12 cases (12.12%) of hanging, semen on glans penis present in 45 cases (50%) of hanging, hyper planter flexion
Keywords: Hanging; Ligature Strangulation; Ligature Mark; Fracture of Hyoid Bone